Partial Pediculectomy for the Treatment of Thoracolumbar Disc Disease - McCartney, W. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
A total of 27 dogs underwent surgery for thoracolumbar intervertebral disc prolapse. A partial pediculectomy was performed in 19 cases. In the majority of these cases the most likely position of the extruded disc material was known from clinical signs and myelography. Eight cases had partial pediculectomy performed as a first stage procedure but ended as a minihemilaminectomy of which in five the position of the extruded disc was known and in three only the disc affected was known. Disc material could be retrieved from the ventral aspect of the spinal cord through a small bony incision in the lateral pedicle without disturbing the area of the vertebral foramen. The advantages of not disturbing the vertebral foramen are avoidance of the branches of spinal artery and the nerve and vessels exiting the foramen making the surgery easier and quicker due to less bleeding.A partial pediculectomy, or modified minihemilaminecto-my was performed on 27 dogs. The location of the disc material in the vertebral canal was ascertained using lumbar myelography and clinical information. If the disc material was lying mainly over the vertebral body the vertebral foramen with its associated blood vessels was not disturbed during surgery, and the disc material was retrieved via a bony incision in the lateral pedicle via a lateral approach.
Keywords: Pediculectomy; hemilaminectomy; disc protrusion; lumbar myelography